Strategi Public Relations PT Pertamina Dalam Pengelolaan Krisis Komunikasi Pada Kasus Depo Pertamina, Plumpang - Puspaningtyas, Raden Roro Nadya; Sumarni, Lilik; Meitana, Nabila Putri; Sulistia, Imelda; Lisnawati, Tamara; Libriyanti, Silvana (HUMANUS : Jurnal Sosiohumaniora Nusantara, 2024)
The tragedy of the fire that occurred at the Pertamina Plumpang Depot in March 2023 resulted in casualties. This incident claimed lives, caused injuries, and led to facility damage and other losses. The root cause of the fire was attributed to various factors, primarily stemming from the use of petroleum products. In responding to this incident, PT Pertamina implemented a strategy that involved providing health assistance, accommodation, and food. Additionally, the company held a press conference on March 4th, 2023, and issued press releases through Pertamina's official YouTube channel. The objective of this research is to understand how Pertamina's crisis communication management unfolded during the Pertamina Plumpang Depot fire issue. The research employed a qualitative method with descriptive analysis. The findings and discussions in this study indicate that the Plumpang Depot fire crisis did not significantly damage the reputation and credibility of PT Pertamina. This was because the company successfully instilled a positive perception among the public, and Pertamina's Public Relations demonstrated responsiveness in handling the case.